Adaptation of infectious bronchitis virus in mammalian cell line - M. J., Suhairoslinda Hayati; Bejo, Mohd Hair; Arshad, Siti Suri; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Infectious bronchitis virus (IBV) is the causative agent of chicken infectious bronchitis (IB), an acute, highly contagious viral respiratory, urinary and reproductive tracts disease. Two different IBV inoculums (UPM1212) preparation was used in the study following inoculation of the virus into African green monkey kidney cell line (Vero cells) up to three consecutive passages. The study showed that the inoculums prepared directly from kidney of IBV infected chicken showed cytophatic effect (CPE) starting from the second (P2) to third passages (P3). The CPE was characterised by formation of syncytium, giant cell, dendritic shaped cell and finally plaque formation. The polymerase chain reaction (PCR) results confirmed the presence of IBV in the Vero cells at P2 and P3. In contrast, no CPE was observed in Vero cells inoculated with inoculums prepared from allantoic fluid following inoculation of the sample into specific pathogen free (SPF) embryonated chicken eggs. The PCR results were negative for IBV.